Carta do Editor - Dowbor, Ladislau; Morais de Oliveira, Felipe; Malheiro Launay, Martha; Camilher Almeida, Fernando (Pesquisa & Debate Revista do Programa de Estudos Pós-Graduados em Economia Política, 2017)
Carta do Editor